Update on non-infectious uveitis treatment: anti-TNF-alpha and beyond - Chauhan, Khushboo; Tyagi, Mudit (Frontiers in Ophthalmology, 2024)
Non-infectious uveitis (NIU) encompasses a range of conditions marked by inflammation within various layers of the eye. NIU is a significant contributor to irreversible vision loss among the working-age population in developed countries. The aim of treating uveitis is to manage inflammation, prevent its recurrences and to restore or salvage vision. Presently, the standard treatment protocol for NIU involves initiating corticosteroids as the primary therapeutic agents, although more aggressive approaches and steroid sparing agent may be necessary in certain cases. These advanced treatments option include synthetic immunosuppressants like antimetabolites, calcineurin inhibitors and alkylating agents. For patients who exhibit an intolerance or resistance to corticosteroids and conventional immunosuppressive therapies, biologic agents have emerged as a promising alternative. Notably, among the biologic treatments evaluated, TNF-α inhibitors, anti-CD20 therapy and alkylating agents have shown considerable efficacy. In this review, we delve into the latest evidence surrounding the effectiveness of biologic therapy and introduce novel therapeutic strategies targeting immune components as potential avenues for advancing treatment of NIU.